2021
DOI: 10.3390/fluids6090332
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network-Based Model Reduction of Hydrodynamics Forces on an Airfoil

Abstract: In this paper, an artificial neural network (ANN)-based reduced order model (ROM) is developed for the hydrodynamics forces on an airfoil immersed in the flow field at different angles of attack. The proper orthogonal decomposition (POD) of the flow field data is employed to obtain pressure modes and the temporal coefficients. These temporal pressure coefficients are used to train the ANN using data from three different angles of attack. The trained network then takes the value of angle of attack (AOA) and pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…It also indicates that the first four modes carry of the total energy. Unlike the circular cylinder [ 70 ] and static airfoils at different angles of attack [ 32 ], where pressure modes are either pairwise symmetric or antisymmetric, the modes in the case of flapping airfoil corresponding to the power generation regime do not exhibit pairwise symmetry or antisymmetry. It is observed that after a symmetric mode about the center line ( ), there is a pair of antisymmetric modes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also indicates that the first four modes carry of the total energy. Unlike the circular cylinder [ 70 ] and static airfoils at different angles of attack [ 32 ], where pressure modes are either pairwise symmetric or antisymmetric, the modes in the case of flapping airfoil corresponding to the power generation regime do not exhibit pairwise symmetry or antisymmetry. It is observed that after a symmetric mode about the center line ( ), there is a pair of antisymmetric modes.…”
Section: Resultsmentioning
confidence: 99%
“…The fractional step method is an effective and strong candidate technique for dealing with incompressible Navier-Stokes equation. It transforms the momentum equation into the convection-diffusion equation and pressure-Poisson equation [32,40,51,66]. We utilize a non-staggered grid in which the velocity and pressure fields are computed at the center of each cell.…”
Section: Discretization Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ahmed et al (2021) developed an ANN-based ROM (ANN-ROM) solver to predict the lift and drag forces for a flow around a circular cylinder. Later, Farooq et al (2021) developed an ANN-ROM to approximate the hydrodynamic forces on NACA-0012 airfoil immersed in a flow field at different angles of attack. The trained model gives accurate values of lift and drag forces compared to true values obtained from direct numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of big data, numerous science and engineering disciplines use dimensionality reduction to obtain lower-dimensional representations of complex physical systems with many degrees of freedom [1][2][3][4][5][6][7][8] . Large data coming from system measurements or simulations is frequently the starting point of reduced-order modeling.…”
mentioning
confidence: 99%